Boundary-value problems for the Lyapunov equation. II - Boichuk, O.; Panasenko, Ye.; Pokutnyi, O. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC517.923 We investigate the bifurcation conditions of the solutions for the nonlinearly perturbed Lyapunov equation. Statements of boundary-value problems are proposed for the coupled systems of Lyapunov equations.